Strategi Penguatan Pendidikan Karakter di Madrasah Diniyah Takmiliyah Ula (MDTU) Nurul Islam Tegal - Afifah Dwi Utami; Hani Alfiana Zain; Dinda Fauziah; Silvia Rizka Lestari; Tria Meriani (La-Tahzan: Jurnal Pendidikan Islam, 2023)
Strategy of strengthening character education in Madrasah Diniyah Takmiliah Ula (MDTU) Nurul Islam Educational Institution Tembok Luwung Village RT 29 RW 06 Adiwerna Subdistrict. This research is a descriptive qualitative research. Data were collected using observation, interview, and documentation techniques. Data validity checking was carried out using triangulation techniques, namely by checking the information from interviews with documentation and observation. The results showed that the strategy of strengthening character education in Madrasah Diniyah Takmiliah Ula (MDTU) Nurul Islam Educational Institution Tembok Luwung Village RT 29 RW 06 Adiwerna District can be done through: integrating values and ethics in subjects, internalizing positive values instilled by all residents of madrasah diniyah, habituation and practice, giving examples and role models, creating an atmosphere of character in madrasah diniyah, and acculturation.